Second Five-Year Plan (1956-61) Delhi - Planning Commission (Planning Commission, 1956)
The recent Conference of Housing Ministers at Sirala-convened by the Union Government and the agenda therfor highlight the anxiety of Central authorities to solve the acute problem of housing. Though the problem has been in existence in the urban areas for quite a time- the Second World war and the Partition have lent it menacing proportions. Generally, the poor section of populace is adversely affected because of their poor rentpaying capacity and as private sector is not interested in constructing accommodation for them. There is, therefore, no other agency excepting the State which can step in and relieve the situation.
Delhi State Secretariat Delhi